(untitled) - Inuhiko, Yomota (New York, 2019)
What might Godzilla and Kurosawa have in common? What, if anything, links Ozu's sparse portraits of domestic life and the colorful worlds of anime? In this book, Yomota Inuhiko provides a concise history of Japanese film that shows how cinema tells the story of Japan's modern age. Discussing popular works alongside auteurist masterpieces, Inuhiko considers films in light of both Japanese cultural particularities and cinema as a worldwide art form. He covers the history of Japanese film from the silent era to the rise of J-Horror in historical, technological, and global contexts. Inuhiko shows how Japanese film has been shaped by traditional art forms such as kabuki theater as well as foreign influences spanning Hollywood and Italian neorealism.
Keywords: Motion pictures,Motion picture plays; History,History and criticism; Japan